KAJIAN YURIDIS TERHADAP PEMBATALAN PERJANJIAN PENGIKATAN JUAL BELI TANAH SAWAH: Juridical Study on the Cancellation of the Binding Agreement for Sale and Purchase of Rice Field Land - Setyawati, Utami; Setiawati, Anda (AMICUS CURIAE, 2024)
The legal act of buying and selling land requires the fulfillment of the elements of light, cash and real as well as material and formal requirements. For material requirements, the seller must be the person whose name is listed in the certificate, while the buyer must qualify as a right holder. Procedurally, PP No. 24/1997 requires that every legal act of land sale and purchase be carried out with an AJB made by a PPAT. If AJB cannot be signed, to bind the parties can make PPJB. In the case of a dispute over a PPJB for a paddy field, the prospective buyer did not want to pay the price and sign the AJB because the certificate had not been changed into the buyer's name. For this problem, the prospective seller demands the cancellation of the PPJB and asks the court to declare the down payment forfeited along with the payment of compensation. In the concept of buying and selling land, the name change can only be done after the AJB is signed. Therefore, the request of the prospective buyer who does not want to sign the AJB cannot be legally justified.